Synthesis of Catalytically Active High Surface Area Sulfated Zirconia - Totok E. Suharto (Jurnal Matematika & Sains, 2003)
A new synthesis method to produce active sulfated zirconia catalyst has been developed. Sulfated zirconium oxide has been prepared by one-step synthesis, where the sulfatation was directly introduced during the gelating step of zirconium hydroxide. The gelating conditions and other synthesis parameters, such as drying and calcination procedures have important influence on the product properties. The obtained sulfated zirconia has high specific surface area, up to 180 m2g-1. The surface area of sulfated zirconia was influenced by increasing of pH-value of the zirconium hydroxide gel in a range of 5 to 9. Active sulfated zirconia catalyst could be prepared by optimalization of synthesis conditions and resulfatation. The catalytic activity of this catalyst in the isomerization of n-butane was higher than the activity of commercial sulfated zirconia and zeolite of mordenite type. The active sulfated zirconia showed a very high selectivity for iso-butane of 85 â 95%, whereas mordenite showed low selectivity of only 40 â 60%. The deactivated catalyst can be simply regenerated by calcination.